OPTIMIZATION OF COAGULATION EFFICACY OF BANANA STEM JUICE IN WATER TREATMENT - Owoicho, Andrew; Shaibu-Imodagbe; I. M Sani (FUDMA JOURNAL OF SCIENCES, 2022)
This work investigates the optimization of coagulation efficacy of banana stem juice as plant natural coagulant in treatment of raw water. Response Surface Methodology was used to optimize the process using Design Expert Version 10. Factors considered were; coagulant dosage (mg/L), retention time (min), and pH with fifteen experimental runs generated using Box Behnken Design method. The parameters analysed were COD, DO, TSS, TDS and Turbidity. Jar test laboratory scale studies was performed and the result analysed statistically to study the effects of pH, retention time and coagulant dosage on coagulation. The coagulation efficacy was achieved at pH 6.5 with percentage removal of 58.065 % after 60 minutes retention time with dosage of 7.5mL/L. Firstly, before carrying these processes, the raw water sample was characterized to ascertain the initial concentration of the parameters before the jar test. Analysis of variance (ANOVA) was used to evaluate the significance of the model and the variables. The model F-value was 12.06 which implies that the model is significant and that there is only a 0.68% chance that such a Model F-value could occur due to interference. Also, values of "Prob > F" were (0.0062) less than 0.0500 indicating that the model terms are significant. It could be concluded that Banana Stem Juice showed tremendous potential as a bio-coagulant for water treatment purposes and could be applied in the pre-treatment stage prior to secondary treatment.